PERENCANAAN DINDING PENAHAN TANAH UNTUK PENGENDALIAN MORFOLOGI TIKUNGAN KALI GEDE DAS SONO KABUPATEN MADIUN - Susilo, Hendro; Rendrarini, Diana (Jurnal Teknik Sipil dan Arsitektur, 2026)
The weir is a vital infrastructure supporting irrigation sustainability by serving as the primary structure for water diversion. Its performance depends heavily on river morphology and channel alignment stability. Morphological changes caused by erosion and sedimentation can alter the river’s course, reducing water diversion effectiveness and decreasing the weir’s capacity to supply irrigation networks. A common phenomenon is the formation of a shortcut channel at river bends, diverting flow away from the weir. This study analyzes channel changes at a bend that reduced weir function and designs a flow control structure to restore the original flow. Conducted at the Kali Gede River in Madiun Regency, where an upstream shortcut diverted the flow, the study employed hydrological analysis to determine design flood discharge using synthetic unit hydrograph methods. Hydraulic analysis via HEC-RAS was performed to obtain flood water elevations. A retaining wall was designed as a flow control structure and evaluated using Geo5 software for stability against overturning, sliding, bearing capacity, and slope stability. HEC-RAS results show that while flood levels remain within sectional capacity, flow tends to bypass through the shortcut. The proposed retaining wall design satisfies all required safety factors for overturning, sliding, and bearing capacity. Thus, constructing a retaining wall to close the shortcut is an effective solution to maintain river morphology and support optimal irrigation weir function.